Investigating the influence of route turning angle on compliance behaviors and evacuation performance in a virtual-reality-based experiment. (April 2021) - Zhang, Ming; Ke, Jinjing; Tong, Liyang; Luo, Xiaowei
Highlights: Performed VR-based evacuation experiments with different route turning angles. Route turning angle negatively affects participants' compliance for emergency signs. Route turning angle affects the difficulty of the participants' perception of exit. Route turning angle influences evacuation speed, pause, and speed deviation. Abstract: Route turning is one of the most essential and ubiquitous physical features in the complex building environment. Under the influence of route turning, evacuees' approaching perspective to an emergency sign could vary, affecting their information perception and behavioral compliance during the evacuation. Although conventional simulation methods assess the effectiveness of the emergency sign in the visible region, they fail to consider evacuees' wayfinding behaviors and interaction with the emergency sign. It remains unclear whether the route turning angle affects evacuees' compliance for detecting and responding to the emergency sign. To investigate such an influence, a virtual-reality-based method for assessing human evacuation behaviors in building fire evacuations was proposed. In this study, two evacuation routes with different turning angles in a shopping mall were created and implemented in a virtual-reality environment, and 67 subjects participated in the immersive virtual-reality-based experiment. All participants took the two routes to find the nearest exit for evacuation in a fire event, aiming to evaluate the effect of the route turning angle on the evacuation process. The participants were asked to complete a questionnaire at the end of the experiment. Next, statistical analyses were conducted on evacuation results, information perception, and evacuation performance of the participants. The results indicated the route turning angle significantly affected participants' behavioral compliance with emergency signs. The results also suggested the route turning angle was influential on participants' information perception and evacuation performance. Besides, a significant effect on rotation change, wayfinding pause, and speed deviation were observed. This study validates the effectiveness of investigating evacuees' interaction with emergency signs using virtual-reality technology and has potential implications for complex building path planning and evacuation simulation modeling.